Analisis Fikih Muamalah dan Undang-Undang Jaminan Produk Halal terhadap Makanan Impor Belum Berlabel Halal - Alya Syifa Utami Handriansyah; Neneng Nurhasanah; Intan Nurrachmi (UNISBA Press, 2023)
Abstract. One proof of attention to Halal Product Assurance on imported products, especially food products, is the existence of Law Number 33 of 2014 concerning Article 4 of Halal Product Guarantee, but imported food is still found circulating without a halal label. With this law, the Muslim community must pay attention to halal in food consumption. This study aims to determine the practice of buying and selling imported food that has not been labeled halal, and analyze the practice of buying and selling imported food in Muamalah Jurisprudence and Law Number 33 of 2014 concerning Halal Product Guarantee. The framework in this study refers to the concept of halal food according to muamalah fiqh and the Halal Product Guarantee Law. This research method is qualitative with an empirical normative approach. The data sources used are primary data in the form of interviews related to the practice of buying and selling imported food that has not been labeled halal and secondary data in the form of books, and journals related to theoretical studies in halal product assurance and certification as well as halal labels of imported products related to this study. The findings of this study are food products that have not been labeled halal in the form of snacks, jelly, cookies. Abstrak. Salah satu bukti perhatian terhadap Jaminan Produk Halal pada produk impor khususnya produk makanan adalah dengan adanya Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal Pasal 4, namun masih ditemukan makanan impor yang beredar tanpa label halal. Dengan Undang-Undang ini masyarakat muslim harus memperhatikan kehalalan di dalam konsumsi makanan. Penelitian ini bertujuan untuk mengetahui praktik jual beli makanan impor yang belum berlabel halal, dan menganalisis praktik jual beli makanan impor dalam Fikih Muamalah dan Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal. Kerangka pemikiran dalam penelitian ini merujuk pada konsep makanan halal menurut fiqh muamalah dan Undang-Undang Jaminan Produk Halal. Metode penelitian ini bersifat kualitatif dengan pendekatan normatif empiris. Sumber data yang digunakan adalah data primer berupa hasil wawancara terkait praktek jual beli makanan impor yang belum berlabel halal dan data sekunder berupa buku, dan jurnal terkait kajian teoritis dalam jaminan produk halal dan sertifikasi serta label halal produk impor yang berkaitan dengan penelitian ini. Temuan penelitian ini terdapat produk makanan yang belum berlabel halal berupa snack, jelly, cookies.